Clinical and Biochemical Parameters of Hemodialysis Patients Before and During Islamic Month of Ramadan (Iranian Journal of Kidney Diseases, 2016)
Introduction. Month of Ramadan bring many changes in life style, especially the diet of Muslims all over the world among both fasting and nonfasting individuals. Hemodialysis patients are kept on restricted diet because of fluid and electrolytes imbalance. The aim of this study was to compare changes in the clinical and biochemical parameters in fasting and nonfasting hemodialysis patients during the Ramadan. Materials and Methods. In a longitudinal study, we recruited 282 patients who were on maintenance dialysis for more than 3 months. Measurements included body weight, blood pressure, serum potassium, serum albumin, and serum phosphorus at the beginning and during the last week of Ramadan. Results. There were 252 patients who were not fasted while 34 patients were those who fasted during the Ramadan. In the nonfasting hemodialysis patients, serum albumin significantly increased at the end of Ramadan (P < .001), while serum phosphorus levels (P = .004) and diastolic blood pressure (P = .002) showed a decrease as compared with the measurements before Ramadan. In the fasting group, only serum albumin had a significant increase (P < .001) during Ramadan, while other parameters were not significantly different between the two measurements. Conclusions. Changes in dietary pattern and content during the Ramadan is safe in terms of electrolyte balance and blood pressure changes for patients on hemodialysis. It is also safe for those patients who want to fast during this month.